The citizen participation as exercise of approach to the construction of civic culture under the right and responsibility (2014)
This paper presents arguments and recognitions of the importance of citizen participation, for defining rights and duties under the assumption that it can build the habit of the community and of the identity of a converging, integrating and facilitating civic culture of socio-economic development. Based on the results of an exercise in citizen participation with high school students in Cartagena de Indias, Colombia, shows the steps from reflection to action, from proposal to implementation.